Pengembangan Technopreneur Produk Pertanian Berbasis Market Place Menuju Masyarakat Ekonomi Kreatif - Rohmaniyah; Alfian, Nurul; Salama Amar, Siti; Subhan; Usman (AMMA : Jurnal Pengabdian Masyarakat, 2023)
Creative economy is a system of human activities related to the creation, production, distribution, exchange and consumption of goods / services that are valuable to market consumers. The development of technopreneurs for market-place-based agricultural products can be a solution to farmers’ problems for the sale of agricultural products and their processing, namely by coordinating agricultural products from farmers by means of (1) Creating centralized management of agricultural products (2) Distributing crops and agricultural processed products through farmer groups and Bumdes (3) Processing crops into products that are ready for consumption with agricultural product processing techniques (4) Bumdes becomes a coordinating forum other than farmer groups to market products and crops (5) Farmer groups coordinate agricultural products and make management for the sale of agricultural products and improve HR management capabilities (6) Increase financial management capabilities.The system of digitizing sales through market places, bringing together buyers and sellers online through E-Commerce without having to rely on location and time in carrying out business transaction processes. Scope of business process analysis from the process of request for information needs to the process of validation of acceptance by consumers. This training makes it easier for the community to promote their agricultural products so that they can add selling value in the market.